Mg/Cr-(COO)22- layered double hydroxide for malachite green removal - Palapa, Neza Rahayu; Badri, Arini Fousty; Mardiyanto; Mohadi, Risfidian; Taher, Tarmizi; Lesbani, Aldes (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
Mg/Cr layered double hydroxide (LDH) was prepared and modified using an intercalation of oxalate anions ((COO)22-) to form Mg/Cr-(COO)22. The materials were then investigated to malachite green removal to determine the adsorption ability. Furthermore, the desorption process and regeneration of adsorbent were systematically conducted. The adsorption of green malachite on Mg/Cr- LDH and Mg/Cr-(COO)22- materials fitted to the pseudo-second-order (PSO) kinetic model and Freundlich isotherm model with an adsorption capacity of 33.784 mg/g (333K) for Mg/Cr LDH and 64.516 mg/g (333K) for Mg/Cr-(COO)22-. Thermodynamic data showed that the adsorption process was spontaneous and endothermic. Also, the appropriate reagent desorption study was found as hydrochloric acid and material regeneration studies exhibited a good recycling performance after 3 times cycles and, the Mg/Cr-oxalate showed a good performance for malachite green adsorption. It can be concluded that Mg/Cr–(COO)22- can adsorb the dye stuffs effectively.